1999
DOI: 10.1046/j.1365-313x.1999.00461.x
|View full text |Cite
|
Sign up to set email alerts
|

FPF1 modulates the competence to flowering in Arabidopsis

Abstract: SummaryDuring the transition to¯owering the FPF1 gene is expressed in the peripheral zone of apical meristems and in¯oral meristems of Arabidopsis. Constitutive expression of FPF1 causes early¯owering in Arabidopsis under both long-day and short-day conditions and leads to a shortened juvenile phase as measured by the trichome distribution on the abaxial leaf surface. In the classical late¯owering mutants, overexpression of FPF1 compensates partially for the late¯owering phenotype, indicating that FPF1 acts do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 53 publications
(76 reference statements)
3
52
0
Order By: Relevance
“…This specific effect on the duration of the juvenile phase is unusual. Other flowering time mutations whose effect on vegetative phase change has been studied have either no effect on the duration of the juvenile phase (Martinez-Zapater et al, 1995;Melzer et al, 1999;Scott et al, 1999;Telfer et al, 1997;Weigel and Nilsson, 1995) or affect the duration of both the juvenile and adult phases of development (Gomez-Mena et al, 2001;Soppe et al, 1999;Telfer et al, 1997). hst-1 is also unusual in that it has a completely opposite effect on flowering time in SD.…”
Section: Discussionmentioning
confidence: 99%
“…This specific effect on the duration of the juvenile phase is unusual. Other flowering time mutations whose effect on vegetative phase change has been studied have either no effect on the duration of the juvenile phase (Martinez-Zapater et al, 1995;Melzer et al, 1999;Scott et al, 1999;Telfer et al, 1997;Weigel and Nilsson, 1995) or affect the duration of both the juvenile and adult phases of development (Gomez-Mena et al, 2001;Soppe et al, 1999;Telfer et al, 1997). hst-1 is also unusual in that it has a completely opposite effect on flowering time in SD.…”
Section: Discussionmentioning
confidence: 99%
“…It was indicated that FPF1 is involved in the GA-dependent signaling pathway (Kania et al, 1997), and it may work synergistically with AP1 and LFY to modulate the competence to flowering in the shoot apical meristem (Melzer et al, 1999). It can promote flowering in Arabidopsis (Kania et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…AGL24, FPF1, and SPL9 promote flowering (Kania et al, 1997;Melzer et al, 1999;Michaels et al, 2003;Schwarz et al, 2008;Wang et al, 2009), whereas FLC, TEM1, TFL1, MAF2, and MAF3 repress flowering (Michaels and Amasino, 1999;Ratcliffe et al, 2003;Castillejo and Pelaz, 2008).…”
Section: Flowering-time Genesmentioning
confidence: 99%